Troubleshooting for Kinked Coronary Catheter: How to Manage? ; A Case Series - Noverike, Nikhen; Satrijo, Budi; Widito, Sasmojo; Kurnianingsih, Novi; Abusari, Muchamad (Universitas Brawijaya, 2023)
Background: Catheter entrapment and knotting are two problems that might arise during coronary angiography, regardless of the method used. It is not uncommon for the catheter shaft to become kinked during diagnostic or interventional procedures. Still, if the manipulation fails, an invasive retrieval method is usually necessary for cases with extensive catheter kinking.Case Illustration: We present two cases illustrating how different angiography approaches could lead to severe catheter kinking. Because of the significant tortuosity of the vasculature, even a gentle opposite rotation maneuver and the antegrade advancement of multiple guidewires failed to untwist the guide catheter. Once a twisted catheter has been identified via fluoroscopy, the twist can be eased by gently twisting the catheter in the opposite direction. It is not always easy. It could lead to using other interventional techniques such as snare, balloon, or surgical procedures. In our cases, we used a snare to snag the catheter's tip and untied the loop's knot. This prevented the need for unscheduled surgical intervention. We evaluated from angiography. There were no further complications. The patients were released from the hospital the following day.Conclusion: Although a kinked catheter could become entrapped, various approaches can be taken to deal with this difficulty and prevent the need for surgical intervention.